Molecular Characterization of Penicillin-Resistant Streptococcus pneumoniae Isolates from Bulgaria - Setchanova, Lena (American Society for Microbiology, 1999)
As part of an ongoing surveillance program of antibiotic-resistant Streptococcus pneumoniae in Sofia, Bulgaria, 120 penicillin-resistant strains (PRSP) (most of them recovered from children hospitalized with pneumococcal disease) were analyzed by microbiological and molecular methods. Several unique features of this collection are of particular interest. (i) Most isolates (112 of 120) were also resistant to trimethoprim-sulfamethoxazole (SXT) (97 of 120 isolates, or 80%), and over 70% (86 of 120) of the isolates were resistant to at least three antibiotics in addition to penicillin. (ii) Close to 80% of all isolates were represented by large clusters of bacteria, each with a unique serotype, antibiotype, and chromosomal macrorestriction pattern (determined by pulsed-field gel electrophoresis), as well as unique restriction fragmentation length polymorphisms of the penicillin-binding protein genes pbp1a, pbp2x, and pbp2b. (iii) A large proportion (45 of 120, or 38%) of the strains belonged to two internationally spread epidemic clones of S. pneumoniae, the first expressing capsular type 23F and the second expressing serotype 9. (iv) A unique Bulgarian cluster composed of eight serotype 19F isolates was resistant to tetracycline, SXT, cefotaxime, and extremely high levels of penicillin and erythromycin. Nevertheless, this clone did not react with either the erm or the mef DNA probes, and thus the mechanism of macrolide resistance in this group of PRSP remains to be elucidated.